PERFORMANCE IN MANAGEMENT OF MEDICAL INSTITUTIONS - SLUSARIUC GABRIELA CORINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2021)
Expectation for performance in management of medical institutions is growing up. Public hospital spending is the fastest-growing area of government expenditure, but its growth can be slowed. The price paid for care is based on the average cost of treatment.A lot of many performance measures and indicators in health management is used in practice and in the literature. The research is performed in the interest of development of the discussion in the medical domain about performance indicator.The finality of the decision-making process is the achievement of the performance.